Analyses on the determinants of elderly workers' plans to retire and desired retirement age. (10th May 2019) - Shin, Moon-Hee; Lee, Young-Min
This study analyses the determinants affecting elderly workers' plans to retire and their desired retirement age, in order to better understand and prepare for their retirement and establish supportive policies. Eighteen years of personal data and additional survey data, provided by the Korean Labor & Income Panel Study, were used for this study. The results of the analysis showed that factors having a significant impact on elderly workers' plans to retire were gender, age, marital status, gross annual earned income after taxes in the past year, subjective health conditions, employment status, financial preparedness for retirement, level of social participation, and overall life satisfaction. The research also revealed that gender, age, education level, marital status, subjective health condition, employment status, and level of social participation impact desired retirement age. Based on the above research results, discussions are offered on policy implications.